Performance and Diet Digestibility of Male Garut Lamb Fed Ipomea reptans Seed - Mohamad Haris Septian; Iman Hernaman; Rachmat Wiradimadja; Fransiskus Teguh Santoso (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The experiments aimed to study about the performance and diet digestibility of male Garut lamb were a diet containing Ipomea reptans seeds. Twenty two Garut sheeps at the age of 6-8 months with an average body weight of 16.17±1.33 kg were divided into four diet treatments containing 0%, 10%, 20%, and 30% Ipomea reptans seed and maintained for 10 weeks to measure the performance and digestibility of the diet. The study was conducted experimentally and the data collected and tested by Duncan’s test. The results showed that the use of Ipomea reptans seeds up to 30% increased (P<0.05) feed intake, average daily gain, dry and organic matter digestibility, but it had no effect on feed conversion. In Conclusion, the use of Ipomea reptans seed up to 30% yielded the best performance and diet digestibility and produced the same quality of diet.